Lingkup Penerapan Asas Hakim bersifat Pasif dan Aktif dalam Pembuktian pada Perkara Perdata di Indonesia - Alya Nur Kamila; Jundiyah Aqilah Rohmah; Falin Kharisma Alya; Sri Handayani (CV. ITTC INDONESIA, 2026)
The purpose of this research is to find out and analyze the evidentiary mechanism in Indonesian civil procedure and the application of the passive and active judge principles within civil adjudication. The study departs from the doctrinal tension between the principles of verhandlungs maxime, dominus litis, and ultra petita partium, which emphasize judicial passivity, and the normative mandates requiring judges to ensure legal certainty (rechtssicherheit), justice (gerechtigkeit), dan usefulness (zweckmassigkeit). The objective of this research is to construct a systematic conceptual reconciliation between judicial passivity in determining the scope of disputes and judicial activism in managing and evaluating the evidentiary process. This research applies a normative juridical method through statutory, conceptual, and principle approaches, analysing the HIR , RBg , Rv, the Civil Code, and Law No. 48 of 2009 on Judicial Power, supported by relevant legal doctrines. The findings show that Indonesian civil procedure is grounded in the pursuit of formal truth under the principle of actori incumbit probatio, whereby judges are bound by the claims and evidence presented by the parties. Nevertheless, judges inevitably exercise an active role in procedural control, evidentiary assessment, and limited fact clarification. The study concludes that judicial passivity and activism function complementarily within a proportional framework to balance legal certainty, justice, and usefulness in civil proceedings.